Anti-roma Bias (Stereotypes, Prejudice, Behavioral Tendencies): A Network Approach Toward Attitude Strength - Sam Nariman, Hadi; Hadarics, Márton; Kende, Anna; Lášticová, Barbara; Poslon, Xenia Daniela; Popper, Miroslav; Boza, Mihaela; Ernst-Vintila, Andreea; Badea, Constantina; Mahfud, Yara; O’Connor, Ashley; Minescu, Anca (Frontiers in Psychology, 2020)
The Roma have been and still are a target of prejudice, marginalization, and social exclusion across Europe, especially in East-Central European countries. This paper focuses on a set of stereotypical, emotional, and behavioral evaluative responses towards Roma people selected as representing the underlying components of anti-Roma bias. Employing network analysis, we investigated, if attitude strength is associated with stronger connectivity in the networks of its constituent elements. The findings from representative surveys carried out in Hungary, Romania, Slovakia, France, and Ireland supported our assumption, as high attitude strength towards the Roma resulted in stronger connectivity in all pairs of high versus low attitude strength networks. Our finding yields a solid theoretical framework for targeting the central variables—those with the strongest associations with other variables—as a potentially effective attitude change intervention strategy. Moreover, perceived threat to national identity, sympathy, and empathy were found to be the most central variables in the networks.